A Full Cycle Length Pseudorandom Number Generator Based on Compositions of Automata - Dömösi, Pál; Gáll, József; Horváth, Géza; Borsos, Bertalan; Tihanyi, Norbert; Alhammadi, Yousef (Informatica, 2021)
In this paper a new Pseudorandom Number Generator based on compositions of abstract automata is presented. We show that it has full cycle with length of 2^128. It is also shown that the output satisfies the statistical requirements of the NIST randomness test suite.